How much will trade liberalization help the poor?: comparing global trade models - Bouët, Antoine (International Food Policy Research Institute, 2006)
Trade liberalization is expected to act positively on development and poverty reduction... The traditional argument in favor of a positive relationship between liberalization and poverty reduction focuses on... [key] linkages. A large proportion of poor people work in the agricultural sector, where trade distortions are particularly high. Liberalization could lead to higher world agricultural prices and raise activity and remuneration in this sector in developing countries. The same beneficial outcome could occur in the textile and apparel sectors, where protection remains high and developing countries have a comparative advantage. But openness can also have negative effects. First, government transfers can shrink as liberalization cuts the government’s receipts of trade-related taxes. Second, terms of trade can deteriorate as liberalization affects world prices. Third, liberalization can impose adjustment costs and raise short-run risk owing to competition from imports and reallocation of productive factors. As a consequence, it is uncertain how much trade liberalization would reduce poverty, and many studies have attempted to assess the size of these benefits. The main empirical tool for this work is the multicountry computable general equilibrium (CGE) model—a sophisticated and complex tool of analysis that often appears as a “black box” from which results are difficult to understand.